An optimized method to measure human FOXP3+ regulatory T cells from multiple tissue types using mass cytometry. Issue 8 (16th May 2018) - Dawson, Nicholas A. J.; Lam, Avery J.; Cook, Laura; Hoeppli, Romy E.; Broady, Raewyn; Pesenacker, Anne M.; Levings, Megan K.
Abstract : We optimized a method to detect FOXP3 by mass cytometry and compared the resulting data to conventional flow cytometry. We also demonstrated the utility of the protocol to profile antigen‐specific Tregs from whole blood, or Tregs from tissues such as cord blood, thymus and synovial fluid.